International Trade Conduct Between Eu-Rf Based on the Sanction Bloc Of Russia-Ukraine Conflict - Siti Rohaya; Henny Septatia Drajati Nugrahani; Thasya Pauline (Journal on Education, 2023)
This study aims to analyze the international economic trade conduct between European Union countries and Russian Federation (RF), especially in the external sector. The Russia-Ukraine conflict destabilizes the international economy in which trade relations between the European Union and RF are in a difficult position. The needs of the European Union for imported commodities originating from RF need to be reviewed, in order to find out how strong international trade relations are from both parties. The finding from international trade conduct that the EU is RF's largest importer of HS27 commodities (Mineral fuels, mineral oil, etc.) with a total of $118 million in 2021, with a 55.9% share of RF's total HS27 exports.